Adequate performing and reporting of a systematic review with meta-analysis: Refractive outcomes after DMEK - Burgueño-Montañes, Carmen (2026)
Presentation: This systematic literature review with meta-analysis by Augustin VA et al. (1), published in the Journal Cataract and Refractive Surgery in 2023 (Q1 in SJR), examines refractive changes after Descemet's membrane endothelial keratoplasty (DMEK). Conclusions: Refractive change after DMEK is widely reported and should be considered during intraocular lens (IOL) calculation prior to cataract surgery alone or combined with DMEK. In the latter case a target refraction of -0.50 D is recommended to achieve emmetropia. Critical comment: The article addresses a very important issue; however, it has several methodological biases, especially related with the bibliographic search strategy, potential biases of included studies and adequate data reporting of the systematic review. The systematic review presented by Augustin VA et al. has poor methodological quality, with several biases and that could compromise the validity of the findings.